Gibalna/športna dejavnost za zdravo družino - Berčič, Herman (Šport (Ljubljana), 2020)
At the end of November 2019, the 14th World Sport for All Congress entitled "Physical/sport activity for a healthy family" was organised in Ljubljana. This title encompasses different issues and problems that were and are still related to a family's sporting, recreational and physical activity. The theme of the congress was discussed from different expert and scientific perspectives that are closely connected to family health. The focus was on the public health and kinesiological (sport science) aspects, whereas some contributions also dealt with the physical/sporting activity of the family from the sociological and economic aspects. Family was also defined in a narrow and a broader sense in terms of the interconnectedness of individual family members of different generations. The main finding of the congress was that families who are more physically active or play more sport are healthier and perform their daily tasks more easily and effectively, as the negative effects of the stressful life are reduced. Due to the above, expert consideration of this theme was both necessary and reasonable. The congress was upgraded with posters and examples of good practices, the quality of which has gradually been increasing.
Keywords: družina; ekonomski vidik; family; gibalna dejavnost; health; javnozdravstveni vidik; kineziološki vidik; physical activity; sociološki vidik; sport; sport activity; šport; športna dejavnost; zdravje